Behavior of geomaterial composite using sugar cane bagasse ash under compressive and flexural loading - Nikhade, Harshal; Birali, Ram Rathan Lal; Ansari, Khalid; Khan, Mohammad Arsalan; Najm, Hadee Mohammed; Anas, S. M.; Mursaleen, Mohammad; Hasan, Mohd Abul; Islam, Saiful (Frontiers in Materials, 2023)
The sugar industry produces a huge quantity of sugar cane bagasse ash in India. Dumping massive quantities of waste in a non-eco-friendly manner is a key concern for developing nations. The main focus of this study is the development of a sustainable geomaterial composite with higher strength capabilities (compressive and flexural). To develop this composite, sugarcane bagasse ash (SA), glass fiber (GF), and blast furnace slag (BF) are used. Ash generated from burning sugar cane in the sugar industry is known as sugar cane bagasse. To check the suitability of this secondary waste for use in civil engineering and to minimize risk to the environment in the development of sustainable growth, a sequence of compressive and flexural strength tests was performed on materials prepared using sugar cane bagasse ash (SA) reinforced by glass fiber (GF) in combination with blast furnace slag (BF) and cement (CEM). The effects of the mix ratios of glass fiber to bagasse ash (0.2–1.2%), blast furnace slag to the weight of bagasse ash (10%), cement binding to bagasse ash (10–20%), and water to sugar cane bagasse ash (55%) regarding the flexural strength, compressive strength, density, tangent modulus, stress–strain pattern, and load–deflection curve of the prepared materials were studied. According to the findings, compressive strength achieved a maximum strength of 1055.5 kPa and ranged from 120 to 1055.5 kPa, and the flexural strength achieved a maximum strength of 217 kPa and ranged from 80.1 to 217 kPa at different mix ratio percentages. The value of the initial tangent modulus for the cube specimens ranged between 96 and 636 MPa. For compression specimens with 20% cement, the density decreased from 1320.1 to 1265 kg/m3, and the flexural strength decreased from 1318 to 1259.6 kg/m3. with limitation in lower percentages of C/SA, the specimen cannot sustain its shape even after curing period. In comparing the previous research with the present experimental work, it was observed that the material proposed here is lightweight and can be utilised as a filler substance in weak compressible soils to improve their load-bearing capacity.